Temporary permanence: the use of refugee camps in protracted refugee situations and its effect on human rights protection - Angwenyi, Samantha Kerubo (AUC Knowledge Fountain, 2013)
Refugees are considered a vulnerable population. As they lack protection from their own countries, it leaves them in need of international protection. This protection is carried out under the international refugee regime which is based on general international human rights law as well as the more refugee-specific international refugee law, both of which strive to ensure human rights protection. Refugee camps are set up as temporary methods of providing protection while durable solutions are sought. However, in recent times, this temporariness is brought into question as protractedness has grown to become a common feature of most refugee situations. The resulting reality is that refugees end up living in camps for longer and longer periods of time. Therefore, it is safe to assume that when refugee camps meet protracted refugee situations, a clash between temporariness and permanence is bound to exist. This thesis aims to explore the effect of this clash has on the refugees in terms of human rights protection. Economic, social and cultural rights were concentrated on as they are believed to have a major impact on the quality of life which resonates with ensuring adequate protection. The analysis is done through drawing examples from different refugee camps around the world. This is followed by a discussion of the findings and suggestions on how refugee agency and participation can be utilized to minimize the effects of this clash of temporariness and permanence.